Ultrathin MoSe2 Nanosheets Confined in N‐doped Macroporous Carbon Frame for Enhanced Potassium Ion Storage. Issue 8 (24th February 2020) - Liu, Yuanlin; Zhai, Yanjun; Wang, Nana; Zhang, Yaohui; Lu, Zhenxiao; Xue, Pan; Bai, Long; Guo, Meiqing; Huang, Di; Bai, Zhongchao
Abstract: Potassium ion batteries (PIBs), as a promising next‐generation electrochemical energy storage device, have drawn great attention in recent years due to the low price and abundant reserves of potassium resource. However, the severe electrode pulverization caused by repeatedly insertion/extraction of large radius of K + hinders their application. Herein a novel strategy is employed to fabricate hierarchical macroporous hybrid composite, ultrathin MoSe2 nanosheets vertical growth on three‐dimension nitrogen‐doped cross‐linked macroporous carbon (HM‐MoSe2 /N−C), via a template route and subsequent selenization process to alleviate the volume expansion and structure pulverization of the electrode. The electrochemical results demonstrate that the HM‐MoSe2 /N−C is a good anode for PIBs including high specific capacity (222.8 mA h g −1 at 0.1 A g −1 ), superior rate capability, and long‐term cycling stability (172.5 mA h g −1 at 0.5 A g −1 after 400 cycles). The extraordinary electrochemical performance of this HM‐MoSe2 /N−C electrode is attributed to the elegant and adequate nanostructure design, which can offer abundant exposed active sites (ultrathin MoSe2 nanosheets), adequate volume accommodation (3D interconnected macropores), and highly conductive carbon frame with fast ion diffusion. Abstract : HM‐MoSe2 /N−C composed by ultrathin MoSe2 nanosheets vertical growth on 3D N‐doped macroporous carbon, prevents the aggregation of nanosheets and accommodates the volume expansion caused by insertion/extraction of K +, enabling high rate performance and long cycling lifespan as anode of PIBs.